Admitting Guilt and Applying Punishment - A Doctrinal Reference to the Lawyers in Criminal Matters - Zarafiu, Andrei (European Scientific Journal, ESJ, 2019)
Within the diverse areas of penal justice, lawyers’ knowledge is applied in the investigation and judgement of criminal matters. Theoretical knowledge is significant because it qualifies the practitioner for the penal procedure provisions interpretation. These skills are essential for practitioners in the field of penal justice, taking into account its main purpose of finding truth and solving the penal cases legally and justifiably: in such a way that the persons who committed offences are convicted in accordance with their guilt, on the one hand, and the innocent ones discharged, on the other hand.